The essence of human potential and its role in the economy - N. A. Baltachеeva (Вестник Северо-Кавказского федерального университета)
The relevance of the research topic is due to the need to study the essence of human potential and the possibilities of managing it in the modern economy. In the era of high dynamism and digitalization of society, highly intelligent production, a person and their potential acquire special importance: qualifications, level of professional training, education, skills and experience become one of the factors of production. Thanks to effective management, the search for new approaches to the formation and development of human potential, the correct understanding of its essence, it becomes possible to build a new system of economic development. The purpose of the study is to analyze the essence of human potential in the modern economy and determine its role for effective use in practical activities. Based on the analysis of scientific literature using such methods as analogy, generalization, synthesis and classification, a semantic analysis of various interpretations of the term under study was carried out, which allowed identifying the features of human potential. Comparative analyses in terms of levels of formation and use, approaches to human potential management, the essence of the terms "human potential", "human capital", "human resources" made it possible to determine the role of a person in reproduction, clearly distinguish the differences between the analyzed terms and determine the specifics of human potential management. Scenarios of innovative development of the state under the influence of human potential have been developed, on the basis of which a matrix of the influence of human potential on the innovative activity of the state has been built. The results obtained can be used as the basis for a new economic model of state management due to the effective formation and development of human potential.